NATIONAL STRATEGIES FOR DIGITIZATION OF HIGHER EDUCATION: A COMPARISON BETWEEN LATVIA AND LITHUANIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Digitization has impacted both countries and shown extensive potential. However, there are differences in both countries in contexts like culture, cognition, tradition, and economic performance among the two countries. The present research has thus developed a comparative scenario of the efforts taken by Latvia and Lithuania to promote and upgrade their higher education sector.  This research has covered peer-reviewed data and comparative scenario of the strategic focus of the strategic focus of national strategies implemented for the digitization of Higher Education, the E-learning structure, the rate of digital and other such aspects in Latvia and Lithuania. The research found that in comparing national strategies for the digitization of higher education between Latvia and Lithuania, both countries demonstrate a commitment to advancing digital education but through distinct approaches. While Lithuania has adopted a more centralized, policy-driven strategy with clearly defined goals for digital transformation; Latvia has taken a more decentralized path, allowing individual institutions more autonomy in their digital initiatives.  The research highlights that while both Latvia and Lithuania are devoted to digitizing higher education, their strategies differ in focus and execution. Latvia's all-inclusive and well-funded method may lead to instant and broad-based digital incorporation. On the other hand, Lithuania's directed approaches could cause in more comprehensive and need-specific results.